P130 The glenfield pleural fluid chart: standardising pleural fluid descriptors for patients and healthcare professionals. (11th November 2022) - Li, D; Johnstone, S; Hinchcliffe, F; Vella, C; Sudhir, R; Panchal, R
Abstract : Pleural effusions are caused by various aetiologies. Pleural fluid can have different appearances. Pleural fluid descriptors are used by healthcare professionals to document the appearance of pleural fluid. There is a wide variety of descriptors used. Our aim was to know the variety of descriptors used, and to create a standardised scale for healthcare professionals and patients. Healthcare professionals locally were asked to describe common pleural fluid appearances. Common descriptors were used to create three colour charts to describe pleural fluid. The charts were provided to patients, carers, and healthcare professionals locally as well as to healthcare professionals nationwide via the UK Pleural Society. Feedback was sought regarding user confidence in describing pleural fluid appearances at baseline and using each chart. Statistical analysis was performed comparing baseline confidence scores with scores using each chart. 7–16 descriptors were received per colour. 73/97 (75%) responders dealt with pleural fluid at least 2–3 times per week. The baseline median confidence score amongst all responders was 8 (interquartile range 7–9). Using the three charts, the median confidence scores were 7 (IQR 5–9), 9 (IQR 8–10) and 10 (IQR 9–10). Statistical analysis was performed using the Wilcoxon Signed-Rank Test. There was a statistically significant difference comparing confidence scores at baseline with chart 2 and chart 3 respectively (p<0.00001). There are minimal resources on how to describe pleural fluid appearances. Whilst our preliminary charts require validation, our project takes the initial steps to providing a standardized chart to educate patients, carers, and healthcare professionals on how to describe pleural fluid and improve communication.